Overlapped Sequence Types (STs) and Serogroups of Avian Pathogenic (APEC) and Human Extra-Intestinal Pathogenic (ExPEC) Escherichia coli Isolated in Brazil - Maluta, Renato Pariz; Logue, Catherine Mary; Tiba Casas, Monique Ribeiro; Meng, Ting; Lopes Guastalli, Elisabete Aparecida; Galvao Rojas, Thais Cabrera; Montelli, Augusto Cezar [UNESP]; Sadatsune, Terue [UNESP]; Ramos, Marcelo de Carvalho; Nolan, Lisa Kay; Silveira, Wanderley Dias da (Public Library Science, 2014)
Avian pathogenic Escherichia coli (APEC) strains belong to a category that is associated with colibacillosis, a serious illness in the poultry industry worldwide. Additionally, some APEC groups have recently been described as potential zoonotic agents. In this work, we compared APEC strains with extraintestinal pathogenic E. coli (ExPEC) strains isolated from clinical cases of humans with extra-intestinal diseases such as urinary tract infections (UTI) and bacteremia. PCR results showed that genes usually found in the ColV plasmid (tsh, iucA, iss, and hlyF) were associated with APEC strains while fyuA, irp-2, fepC sitD(chrom), fimH, crl, csgA, afa, iha, sat, hlyA, hra, cnf1, kpsMTII, clpV(Sakai) and malX were associated with human ExPEC. Both categories shared nine serogroups (O2, O6, O7, O8, O11, O19, O25, O73 and O153) and seven sequence types (ST10, ST88, ST93, ST117, ST131, ST155, ST359, ST648 and ST1011). Interestingly, ST95, which is associated with the zoonotic potential of APEC and is spread in avian E. coli of North America and Europe, was not detected among 76 APEC strains. When the strains were clustered based on the presence of virulence genes, most ExPEC strains (71.7%) were contained in one cluster while most APEC strains (63.2%) segregated to another. In general, the strains showed distinct genetic and fingerprint patterns, but avian and human strains of ST359, or ST23 clonal complex (CC), presented more than 70% of similarity by PFGE. The results demonstrate that some "zoonotic-related'' STs (ST117, ST131, ST10CC, ST23CC) are present in Brazil. Also, the presence of moderate fingerprint similarities between ST359 E. coli of avian and human origin indicates that strains of this ST are candidates for having zoonotic potential.